El impacto socio-afectivo en las familias de pacientes oncológicas de cáncer de mama, del instituto regional de enfermedades neoplásicas - Trujillo. 2017. - López Bazán, Karent Yolanda (2017)
This thesis was conducted with the purpose of explaining the socio-affective in the families of oncological patients of breast cancer of the Regional Institute of Neoplastic Diseases, during the year 2017. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 10 relatives of oncological patients of breast cancer, which work by applying the methods and techniques of quantitative and qualitative investigation. The results show that these families of the oncological patients of breast cancer, have a certain disregard for breast cancer treatment, difficulties in the control of your emotions and fear the worst of this disease and leads to family adjustment of patients who are being treated in the Regional Institute of Neoplastic Diseases of Trujillo. The confirmation of the diagnosis of breast cancer leads to the affected woman and her family to meet with difficult decisions and confrontations. This disease becomes a major challenge in the life of a family, since none of the Member States remains intact, causing, sometimes, changes in the couple relationship when there are settings set between them, which imposes a significant challenge to the ability of the family group to be kept relatively organized as it adjusts to the diverse needs.